2017
DOI: 10.18632/oncotarget.v8i70
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Besides their structural role, sphingolipids including Sphingosine-1phosphate (S1P) have drawn attention as bioactive sphingolipid signaling molecules involved in the regulation of several processes, including cell growth, differentiation, survival, migration or immune response. It is now well established that S1P is involved in the onset or the progression of pathological conditions such as cancer, autoimmunity, cardiovascular conditions or diabetes to name a few. The S1P content in cells is low and is kept u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…In heart tissue, melatonin and celecoxib attenuate inflammation-induced cardiac hypertrophy 50,51. Melatonin and celecoxib execute their effects by several mechanisms, such as inflammasomes and Wnt and BMP pathways 5254. Moreover, further studies are required to investigate whether similar mechanisms are involved to mediate the effects of melatonin and celecoxib in ethanol-induced neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In heart tissue, melatonin and celecoxib attenuate inflammation-induced cardiac hypertrophy 50,51. Melatonin and celecoxib execute their effects by several mechanisms, such as inflammasomes and Wnt and BMP pathways 5254. Moreover, further studies are required to investigate whether similar mechanisms are involved to mediate the effects of melatonin and celecoxib in ethanol-induced neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Although the upregulation of PSAT1 was the focus of this study, Rylaze treatment upregulated other notable genes including CHAC1, ADM2, CTH, and S100P. Among these, CHAC1, an ATF4 target gene activated by the amino acid response pathway, is involved in glutathione degradation and ferroptosis (47,48). The upregulation of CHAC1 following PHGDH silencing has been implicated in breast cancer, and in AML; its overexpression is associated with high-risk prognosis and reduced overall survival (47,49).…”
Section: Discussionmentioning
confidence: 94%
“…Among these, CHAC1, an ATF4 target gene activated by the amino acid response pathway, is involved in glutathione degradation and ferroptosis ( 47 , 48 ). The upregulation of CHAC1 following PHGDH silencing has been implicated in breast cancer, and in AML; its overexpression is associated with high-risk prognosis and reduced overall survival ( 47 , 49 ). Conversely, S100P, a calcium-binding protein, showed positive correlation with overall survival in AML patients, suggesting its potential as a novel biomarker and prognostic factor in AML ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of cfDNA levels for EC screening and classification appears to be controversial. Significantly elevated total cfDNA levels were detected in EC group compared with the controls, with higher levels in high-grade groups (G2 and G3) 39. Another study reported a dramatic difference between the mean level of cfDNA in patients with type I and type II EC 40.…”
Section: Application Of Cfdna/ctdna In Ovarian and Endometrial Cancermentioning
confidence: 94%